(3GdEMSGf aj JbQjH UMjM GHf MHGfs - (3Ydj Hf HdHGf Hf YHO Gddg, YdGA GdOjf GdaGQSqj, GdefYhJ HGdCejQ, J (B739 (3g` s
(3ChdgG (B:s
(3jHJOF HcJGH GdSjQ s
(3BNQgG (B:s
(3hjfJgi HGdENHGQ Yf fai ONhd GdLfI deDef HGdSMQ s
(3cJH Ydi gPG GdLRA Cfg GdQGHYs
(3hgh HNW eZGjQ ddGLRGA GdJi bHdgs
(3hdcfg jced GdfbU GdPi Hjf GdLRGjf GdSGOS hGdKGef hdPdc CYJHQ GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B267 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B48s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B32 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B54 s
Keywords: (3GdMOjK h GdeUWdMs